Geophysical and geochemical analysis of shallow gas and an associated pockmark field in Bantry Bay, Co. Cork, Ireland. (30th September 2019) - Jordan, S.F.; O'Reilly, S.S.; Praeg, D.; Dove, D.; Facchin, L.; Romeo, R.; Szpak, M.; Monteys, X.; Murphy, B.T.; Scott, G.; McCarron, S.S.; Kelleher, B.P.
Abstract: An integrated geophysical, geological, and geochemical investigation of seabed fluid venting was carried out in upper Bantry Bay, a large marine inlet on the southwest coast of Ireland. The results provide evidence of the seafloor venting of gas rich fluids, resulting in the formation of a pockmark field identified here for the first time. The pockmarks occur in an area where sub-bottom profiles provide evidence of chimney-like features interpreted to record upward gas migration through Quaternary sediments to the seafloor. Three vibrocores up to 6 m long were acquired in water depths of 24–34 m, two from the pockmark field and one from outside. Methane of predominantly biogenic origin was quantified in all three cores by headspace analysis of sediment sub-samples. Well-defined sulfate methane transition zones (SMTZs) were observed in two of the cores, the shallowest (1.25 m below sea floor (mbsf)) inside the pockmark field and the other (3.75 mbsf) outside. It is likely that an SMTZ occurs at the location of the third core, also within the pockmark field, although deeper than the samples obtained during this study. Gas migration towards the seafloor is suggested to involve both diffuse pore fluid migration across wide areas and focused flow through the pockmarks, together driven by methanogenesis of pre-glacial lacustrine sediments preserved in a bedrock basin, and possible gas release from the Owenberg River Fault. Analysis of phospholipid fatty acids (PLFAs) and archaeal isoprenoid hydrocarbons was used to investigate the microbial ecology of these sediments. Anaerobic oxidation of methane (AOM) may play a role in controlling release of CH4 to the water column and atmosphere in this shallow gas setting, potentially mediated by syntrophic sulfate reducing bacteria (SRB) and anaerobic methanotrophic archaea (ANME). Highlights: Acoustic data provided evidence for widespread fluid seepage in a shallow marine bay in Co. Cork, Ireland. Fluid migration has led to the formation of a previously undescribed pockmark field within the bay. Ground-truthing showed fluid as biogenic methane, possibly derived from methanogenesis of pre-glacial lacustrine sediments. Microbial anaerobic oxidation of methane plays key role in controlling release of methane to the atmosphere from the bay.